Pengaruh Self Assessment System terhadap Kepatuhan Wajib Pajak Orang Pribadi - Neni Nur Fitriani; S Mia Lasmaya; Iwan Sidharta (Center of Research, STIE Pasundan, Bandung, Indonesia., 2021)
This study aims to determine the implementation of the self-assessment system, determine the compliance of individual taxpayers, and find out how much influence the self-assessment system has on individual taxpayer compliance. The method used in this research is the descriptive analysis method. The technique used in collecting data is done through a questionnaire with 32 respondents as KPP Pratama employees in Bandung. The data analysis technique carries out through descriptive analysis and verification analysis. The study results found that the self-assessment system was in the relatively good category with an average score of 3.14 and for individual taxpayer compliance was in the relatively good category with an average score of 3.06. Then the self-assessment system is said to be adequate in increasing individual taxpayer compliance, proven to affect individual taxpayer compliance by 46.0%. In comparison, the remaining 54.0% influence by other factors not examined in this study, such as the administrative system's condition, taxation, services to taxpayers, tax law enforcement, tax rates, and so on. Thus it can be concluded that there is an effect of the self-assessment system on individual taxpayer compliance.